Bilingual Identity Construction through Social Media: A Study of English Influenced Code Mixing - Abdul Rahman; Gunawan Gunawan; Dian Riani Said; Mardi Mardi (Jurnal Studi Guru dan Pembelajaran)
Code-mixing on social media is a complex phenomenon that is not merely caused by limited proficiency in Indonesian or English but is also influenced by various social and psychological factors. In today’s digital and globalized era, understanding how code-mixing contributes to the construction of bilingual identity is crucial, especially given the increasing cross-language interactions on online platforms. Therefore, this study aims to examine the role of English-influenced code-mixing in shaping the bilingual identity of social media users. This research employs a qualitative approach with a single embedded case study design conducted at Universitas Cahaya Prima Bone. The participants consisted of 15 second-semester students selected through purposive sampling and 3 English lecturers or linguists knowledgeable about bilingualism and digital communication. Data were collected through semi-structured interviews and analyzed using data reduction, presentation, conclusion drawing, and triangulation to ensure validity. The findings reveal that code-mixing practices on social media reflect complex socio-cultural dynamics and function as an effective communication strategy as well as a means of constructing bilingual identity in the digital era. Code-mixing also enhances expressive abilities and supports informal English learning and vocabulary development. However, uncontrolled use of code-mixing in formal academic contexts may cause issues related to grammatical accuracy and language consistency. This study offers practical contributions to language education development and identity studies in the digital age by emphasizing the importance of approaches that integrate linguistic understanding and identity construction within online communication environments.